(a+2b)^2(a-2b)^2-(2a+b)^2(2a-b)^2 化简
来源:学生作业帮助网 编辑:六六作业网 时间:2024/12/19 04:10:50
(a+2b)^2(a-2b)^2-(2a+b)^2(2a-b)^2化简(a+2b)^2(a-2b)^2-(2a+b)^2(2a-b)^2化简(a+2b)^2(a-2b)^2-(2a+b)^2(2a-b
(a+2b)^2(a-2b)^2-(2a+b)^2(2a-b)^2 化简
(a+2b)^2(a-2b)^2-(2a+b)^2(2a-b)^2 化简
(a+2b)^2(a-2b)^2-(2a+b)^2(2a-b)^2 化简
(a+2b)^2(a-2b)^2-(2a+b)^2(2a-b)^2
=(a²-4b²)²-(4a²-b²)²
=(a²-4b²+4a²-b²)(a²-4b²-4a²+b²)
=(5a²-5b²)(-3a²-3b²)
=-15(a²-b²)(a²+b²)
=-15a^4+15b^4
如果本题有什么不明白可以追问,
(a+2b)^2(a-2b)^2-(2a+b)^2(2a-b)^2
=(a^2-4b^2)^2-(4a^2-b^2)^2
=a^4-8a^2b^2+16b^4-16a^4+8a^2b^2-b^4
=-15a^4+15b^4
-2a(a+b)+b(a+b)
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
化简:a-[b-2a-(a-b)]
化简(2a-b/a+b-b/a-b)÷a-2a/a-b
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b]
-a-b+2b^2/a+b
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/a]
化简:[2/3a - 2/(a+b) * (a+b/3a - a - b)] / (a-b)/a
(a/a-b-a/a+b)(a+b)(a-b)/2b
(b-a)*(b-a)+(b-a)*2*a等于多少?
化简:|a+b|+|b-a|+|2b|
|a+b|-|b-a|+|2b|化简哦!
a-b+2b²/a+b
通分a-b,2b^/a+b
化简(2a-b/a+b-b/a-b)除以a-2b/a+b
计算:((a+b)(a-b)-(a-b)^2+2b(a-b))/4(a-b)
化简(2a-b/a+b-b/a-b)除以a-2b/a +b